2020
DOI: 10.1007/s10518-019-00777-z
|View full text |Cite|
|
Sign up to set email alerts
|

Seismic site effects in the Red Zone of Amatrice hill detected via the mutual sustainment of experimental and computational approaches

Abstract: This paper presents the results of numerical analyses of ground motion in the Red Zone sector of Amatrice hill, violently struck by the 2016-2017 Central Italy seismic sequence. The methodologies used in processing the data to define the numerical model are firstly described. The results obtained from the computational analyses are then presented and discussed by comparing them with experimental data set of weak motion recordings. Computational analyses were performed via both a 2D-numerical FEM model and a ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Here, the amplification is larger in the northern sector and varies from the central part to the edge, where [25] observed a clear directionality of the resonant peak (on the contrary, [34] concluded that maximum directions are linked to the presence of noise sources). These observations suggest a lateral variability of the geological conditions, due to the spatial variation of the impedance contrast, and the presence of topographic effects, due to the morphology of the area [25,29,30]. quake a few hundred meters away from the historical center (AMT station).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Here, the amplification is larger in the northern sector and varies from the central part to the edge, where [25] observed a clear directionality of the resonant peak (on the contrary, [34] concluded that maximum directions are linked to the presence of noise sources). These observations suggest a lateral variability of the geological conditions, due to the spatial variation of the impedance contrast, and the presence of topographic effects, due to the morphology of the area [25,29,30]. quake a few hundred meters away from the historical center (AMT station).…”
Section: Introductionmentioning
confidence: 87%
“…This short review highlights that there is no single interpretation on the explanation of the ground motion experienced in Amatrice, neither on the causes of the variability of heavy damage [25,29,30,34]. Indeed, the ground motion complexity, due to a combination of nearsource and site effects, is difficult to reproduce with standard simulation techniques [21,29].…”
Section: Figure 1 (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…Ground motion prediction maps, referred to the Central Italy event occurred on August 24, 2016, (i.e., the first destructive event of the Central Italy seismic sequence for which a great amount of studies have been published) are shown in § 4 to enlighten the capability of the proposed ML approach to gauge the ground motion variability at the urban scale. Moreover, with reference to § 4.1, the ground motion profiles, based on the proposed ML approach, are compared with results obtained by means of two completely different methodologies: 2D numerical modelling of seismic site response (Gaudiosi et al, 2021;Giallini et al, 2020;Grelle et al, 2020) and with the mean values predicted by the Italian ShakeMaps (http://shakemap.rm.ingv.it/shake4/). Finally, in the § 4.2, referring to the seismic event occurred on October 30, 2016 (i.e., the strongest of the Central Italy seismic sequence), the spatial correlation structures of the maps are analyzed in terms of sill and range in order to provide the relation between local site effects and spatial resolution of ground motion maps.…”
Section: Introductionmentioning
confidence: 99%